2021
DOI: 10.1108/ecam-09-2020-0678
|View full text |Cite
|
Sign up to set email alerts
|

Administrative risks challenging the adoption of smart contracts in construction projects

Abstract: PurposeAs a remedy to usually voluminous, complicated and not easily readable construction contracts, smart contracts can be considered as an effective and alternative solution. However, the construction industry is merely known as a frontrunner for fast adoption of recent technological advancements. Numerous administrative risks challenge construction companies to implement smart contracts. To highlight this issue, this study aims to assess the administrative risks of smart contract adoption in construction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 103 publications
1
29
0
Order By: Relevance
“…Nevertheless, the authors listed technical risks, such as vulnerability, criminal activity and exposure of identities, that can put the construction industry under threat, but the authors did not provide us with an evaluation of identified risks. The findings of Gurgun and Koc (2021) show that smart contract posed significant risks to construction projects and project-based organizations in terms of (1) regulation change in planning, (2) lack of a driving force in management, (3) activities are not accounted in planning, (4) deficiencies in legal arrangements and (5) weak dispute resolution mechanism. Li et al (2019) mentioned some blockchain risks overshadowing construction without any evaluation and discussion, such as malicious attacks, the threat of tampering and manipulating devices, and job security due to automation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the authors listed technical risks, such as vulnerability, criminal activity and exposure of identities, that can put the construction industry under threat, but the authors did not provide us with an evaluation of identified risks. The findings of Gurgun and Koc (2021) show that smart contract posed significant risks to construction projects and project-based organizations in terms of (1) regulation change in planning, (2) lack of a driving force in management, (3) activities are not accounted in planning, (4) deficiencies in legal arrangements and (5) weak dispute resolution mechanism. Li et al (2019) mentioned some blockchain risks overshadowing construction without any evaluation and discussion, such as malicious attacks, the threat of tampering and manipulating devices, and job security due to automation.…”
Section: Discussionmentioning
confidence: 99%
“…For this, the authors used the SWOT framework to analyze strengths-weaknesses-opportunitiesthreats caused by blockchain. Gurgun and Koc (2021) targeted administrative risks of smart contracts in construction projects. The authors employed fuzzy analytic hierarchy process (AHP) to determine weights of managerial, planning, contractual, relational and cultural criteria.…”
Section: Introductionmentioning
confidence: 99%
“…This study adopted the triangular fuzzy numbers (TFN) in the FAHP application since its implementation was first ensured by the Chang (1996). In addition, the triangular fuzzy AHP has widely been for a variety of objectives in the construction management literature such as risk assessment of smart contract (Gurgun and Koc, 2021), building supplier selection (Plebankiewicz and Kubek, 2016), assessment of quality management systems (Lam et al, 2008) and risk assessment of tunnel project (Lyu et al, 2020).…”
Section: Strategy Evaluationmentioning
confidence: 99%
“…The results suggest that four factors have a significant influence on the adoption of smart contracts: supply chain pressure, competitive pressure, support from upper management, and the possibility to monitor it. 2 (Gurgun & Koc, 2021). This study seeks to evaluate the administrative risks of adopting smart contracts in construction projects.…”
Section: Inclusion Criteria Exclusion Criteriamentioning
confidence: 99%